2004
DOI: 10.1021/jp0491616
|View full text |Cite
|
Sign up to set email alerts
|

Acid−Base Equilibrium Constants and Distribution Coefficients of Aminopyrene between the Surface and Bulk of Liquid Water as Studied by a Laser Two-Photon Ionization Technique

Abstract: The pH-dependent amount of aminopyrene adsorbed at the water surface was measured using a laser twophoton ionization technique. The distribution coefficients of neutral and cationic aminopyrene between the surface and bulk of liquid water were determined to be 9.6 × 10 -6 m and 2.5 × 10 -7 m, respectively. The acid-base equilibrium constant, pK a , of aminopyrene on the water surface was determined to be 2.0, while that of the same molecule in bulk water was 3.6 ( 0.1. These results show that neutral aminopyre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Such a trend has been experimentally demonstrated in the basicity of small molecular arylamines. For example, p K a for the conjugate acid of aniline in water is 4.62, for 1-naphthylamine is 3.92, and for amino-pyrene is 3.6 . Thus, for Re complexes with diamine ligands of increasing size, the energetic advantage of the proton-coupled pathway over the unprotonated one will decrease.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Such a trend has been experimentally demonstrated in the basicity of small molecular arylamines. For example, p K a for the conjugate acid of aniline in water is 4.62, for 1-naphthylamine is 3.92, and for amino-pyrene is 3.6 . Thus, for Re complexes with diamine ligands of increasing size, the energetic advantage of the proton-coupled pathway over the unprotonated one will decrease.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Commonly used experimental methods for studying the water surface pH are spectroscopic methods: second-harmonic generation, [9][10][11] vibrational sum-frequency generation, [12][13][14] heterodyne-detected electronic sum-frequency generation, 15 and two-photo ionization 16 were used to clarify the acidity of the air/ water interface. Mostly, they showed that the water surface pH is more acidic.…”
Section: Introductionmentioning
confidence: 99%